SYRIAN CRISIS: FRENCH-AMERICAN POSITION - Юрчак, В. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article analyzes the Franco-American position on resolving the conflict in Syria. The reasons of military non-intervention of the French Republic and the United States in the Syrian conflict were examined and the author shows the Franco-American cooperation on the Syrian crisis after the use of chemical weapons against the Syrian population.